Protein O-GlcNAcylation Promotes Trophoblast Differentiation at Implantation - Peter T. Ruane; Cheryl M. J. Tan; Daman J. Adlam; Susan J. Kimber; Daniel R. Brison; John D. Aplin; Melissa Westwood (Cells, 2020)
Embryo implantation begins with blastocyst trophectoderm (TE) attachment to the endometrial epithelium, followed by the breaching of this barrier by TE-derived trophoblast. Dynamic protein modification with O-linked β-N-acetylglucosamine (O-GlcNAcylation) is mediated by O-GlcNAc transferase and O-GlcNAcase (OGA), and couples cellular metabolism to stress adaptation. O-GlcNAcylation is essential for blastocyst formation, but whether there is a role for this system at implantation remains unexplored. Here, we used OGA inhibitor thiamet g (TMG) to induce raised levels of O-GlcNAcylation in mouse blastocysts and human trophoblast cells. In an in vitro embryo implantation model, TMG promoted mouse blastocyst breaching of the endometrial epithelium. TMG reduced expression of TE transcription factors Cdx2, Gata2 and Gata3, suggesting that O-GlcNAcylation stimulated TE differentiation to invasive trophoblast. TMG upregulated transcription factors OVOL1 and GCM1, and cell fusion gene ERVFRD1, in a cell line model of syncytiotrophoblast differentiation from human TE at implantation. Therefore O-GlcNAcylation is a conserved pathway capable of driving trophoblast differentiation. TE and trophoblast are sensitive to physical, chemical and nutritive stress, which can occur as a consequence of maternal pathophysiology or during assisted reproduction, and may lead to adverse neonatal outcomes and associated adult health risks. Further investigation of how O-GlcNAcylation regulates trophoblast populations arising at implantation is required to understand how peri-implantation stress affects reproductive outcomes.